Attention to Detail: The Effect of Fluoroscopic Parallax on Limb Alignment Assessment During Corrective Osteotomy. (13th February 2023) - Weldon, Matthew; Arenas, Abraham; Abraham, Alex; Haidar, Layla A.; Warth, Ryan J.; Mansour, Alfred
Abstract : Background: The accuracy of a corrective osteotomy is dependent on many factors. One error rarely considered is using noncentered fluoroscopic imaging to assess intraoperative alignment. This study quantified the coronal alignment error produced by visual parallax per interval changes in vertical and horizontal positioning of the C-arm and alignment rod during intraoperative evaluation. Methods: Unilateral hip, ankle, and knee fluoroscopic images were obtained from a single intact cadaveric specimen. A center-center fluoroscopic image was obtained by moving the C-arm appeared in the center square of the nine-box grid. With the base of the C-arm stationary, the radiograph generator/intensifier portion of the C-arm was translated medially until the target bone appeared on the edge of the fluoroscopic image. Results: One hundred eight images were obtained. Measurement error increased by an average of 14% per 10 mm of horizontal C-arm offset. Minimal effect was seen if the obtained image was within 5 mm of the true center; however, once 55 mm of offset was reached, all experimental conditions resulted in at least 10 mm of parallax error. Conclusion: Our results demonstrate that small variations in C-arm positioning can create statistically significant inaccuracies when assessing limb alignment using intraoperative fluoroscopy.